Peran Pemerintah dalam Pengembangan dan Peningkatan Ekspor Rempah Nusantara: Analisis Hukum dan Kebijakan Publik di Indonesia - Fitri Herdayani; Masayu Adiah; Novita Wulandari (Universitas Medan Area, 2026)
Spices are a strategic commodity that has important historical, economic, and geopolitical value for Indonesia. Although Indonesia is known as one of the world's main spice producers, the spice sector's contribution to the national economy and export performance has not been optimal. This research aims to analyze the role of the government in the development of the archipelago's spice potential as well as the policies and regulations taken to increase the competitiveness and export of spices in the global market. The research method used is normative legal research with a statutory approach and a policy approach, supported by secondary data in the form of laws and regulations, policy documents, official government reports, and relevant scientific literature. The results of the study show that the government has established various strategic policies in the development of the spice sector, but their implementation still faces obstacles in the form of weak institutional coordination, limited supporting infrastructure, and suboptimal protection and support for farmers and spice business actors. Therefore, it is necessary to strengthen integrated policies, harmonize regulations across sectors, and increase regulatory and fiscal support to optimize the potential of the archipelago's spices in a sustainable manner. The conclusion of this study emphasizes that an active, consistent, and integrated government role is the main key in encouraging the increase of competitiveness and export of Indonesian spices